Kansas. Forestry - Kellogg, George Henry (My University, 1905)
Introduction: The world of today is constantly called upon to rectify the mistakes of the past. These mistakes often involve great problems but the progress of the ages is measured by the solutions. We cannot hope to solve all of the problems presented but must take them in the order of their importance. One of the foremost problems of today is how to secure a future timber supply. The treatment of timber for many years has been mainly in the wrong direction and this careless and unwise policy has gathered such great momentum as to nearly bankrupt our future timber business in these United States. The carelessness, ignorance and maliciousness of our white people have been equaled only by the savage. Immense fortunes have been destroyed each year by fire alone and the greater number was set intentionally, either from revenge or for sport. Many a fortune has been thus consumed because a few people wanted to make their berry patches or hunting ground more profitable. Lumbermen have sought immediate profits and have almost shut themselves from future business. They have battered the best forests with increasing efforts until the finer woods are fast becoming a thing of the past, and they walk about with an eager eye in search of the next best substitute. Necessity is the mother of invention and the time is ripe for action. Fire, lumbering, turpentine-orcharding, tanneries, paper factories and grazing have brought us in sight of a lumber famine and the man of brains is now looking for a way out. Forests that were heretofore greatly unprofitable and inaccessible are now penetrated under great expense, the prices for lumber advance steadily no increase in profits.
Citation: Kellogg, George Henry. Kansas. Forestry. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Forests; Rail Road Companies; Soil Fertility; Theses